Risk Management in Construction Projects (IntechOpen, 2021)
A project risk could be described as anything that could impact the fundamentals of a project performance timeline, performance, or budget. So, risk management, then, could be described as the deliberate processes of identifying, categorizing, prioritizing, and planning for risk occurrences before they disrupt project delivery. This book has contributions from diverse fields in the construction sector. What makes it even more interesting is that they all come from different countries and regions, making the narrative more eclectic and yet at the same time stimulatingly rich. This is the time when we have to assess the way we understand and manage construction industry risk as we transition to the new era of the fourth industrial revolution.